2016
DOI: 10.1007/s00221-016-4716-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lower limb proprioceptive sense and locomotor skill acquisition

Abstract: Sensorimotor integration is essential for controlling movement and acquiring new motor tasks in humans. The aim of this project was to understand how lower limb proprioceptive sense contributes to the acquisition of a skilled walking task. We assessed lower limb joint position and movement detection sense in healthy human subjects using the Lokomat robotic exoskeleton. Subjects walked on a treadmill to practice a skilled motor task (200 trials) requiring them to match their foot height during the swing phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…The m-iSCI participants demonstrated a high level of performance accuracy in the precision walking task after training. Performance errors in the posttraining test corresponded to a range from 10 to 30 mm, which is comparable to the age-matched controls at 12-37 mm, as well as our previous study with young adults at 13-37 mm (Qaiser et al 2016). In a similar locomotor task, people could precisely step over an obstacle with a clearance height as low as 20 mm after practicing with auditory feedback (Erni and Dietz 2001;Lam and Dietz 2004;van Hedel et al 2002).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The m-iSCI participants demonstrated a high level of performance accuracy in the precision walking task after training. Performance errors in the posttraining test corresponded to a range from 10 to 30 mm, which is comparable to the age-matched controls at 12-37 mm, as well as our previous study with young adults at 13-37 mm (Qaiser et al 2016). In a similar locomotor task, people could precisely step over an obstacle with a clearance height as low as 20 mm after practicing with auditory feedback (Erni and Dietz 2001;Lam and Dietz 2004;van Hedel et al 2002).…”
Section: Discussionsupporting
confidence: 84%
“…During performance of the task, participants used JPS at the hip and knee to accurately position their foot to the target height. Our previous study also demonstrated a relationship between JPS and performance of the task among able-bodied adults (Qaiser et al 2016). Similarly, in the stroke literature, studies have reported that the degree of proprioceptive deficits in the upper limbs is directly related to the motor learning capacity of tracking tasks (Vidoni and Boyd 2009).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The qualitative reports [9,57], laboratory studies [11][12][13] and clinical approaches [14], which emphasise the importance of accurate somatosensory information to movement, could not be fully supported.…”
Section: Discussionmentioning
confidence: 99%
“…To successfully adapt to altered walking terrains, avoid obstacles and manage slopes for example, somatosensory information such as changes in foot plantar pressures, lower limb positions, and limb/foot loading must be detected, relayed, and integrated by the Central Nervous System (CNS) [10]. Laboratory studies have shown that altered somatosensation in the lower limb, independent of motor weakness, impacts postural regulation [11], foot placement [12], and obstacle avoidance performance error [13]. Thus, clinical interventions acknowledge the importance of accurate somatosensory feedback in the rehabilitation of movement post stroke [14] and case studies of those with tactile and proprioceptive deficits and intact motor pathways, due to central [15] or peripheral [16,17] neurological deficits, report substantially impaired motor function, gait, and spatial orientation.…”
Section: Introductionmentioning
confidence: 99%